THE FORMATION OF THE ARCHETYPE "MAHNA MATER" IN UKRAINIAN CULTURE - Матюхіна, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The author of the article examines the sources of formation of the archetype "Mahna Mater" in Ukrainian culture.